ANALISIS PENERAPAN STANDAR AKUNTANSI DALAM LAPORAN KEUANGAN USAHA MIKRO KECIL DAN MENENGAH DI KABUPATEN PASURUAN - Riski Amilia; Noor Shodiq Askandar; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis study aims to determine the application of accounting standards for small and medium micro entities in MSMEs Financial Reports in Pasuruan District. This research method uses descriptive qualitative. The population of this study amounted to 30 MSMEs and the sample in this study amounted to 11 MSMEs in Pasuruan Regency. The data used are secondary data in the form of MSME financial reports in Pasuruan Regency. The results of the study show that in general the research conducted by MSMEs has not found conformity in implementing EMKM IFRSs in MSME financial reports, where standard financial accounting for small and medium micro entities has been published by Indonesian accounting ties as a standard in preparing financial reports specifically for MSMEs as a means of facilitating other arrangements and interests.Keywords: SAK EMKM, UMKM, Financial Report